PARENTING PARENTS RELATIONSHIP WITH EMOTIONAL INTELLIGENCE MANAGEMENT OF CHILDREN AGES 3-5 YEARS IN THE VILLAGE SEMBUNG WEDI KLATEN - Tri Purwaningsih; Sumantri .; Titis Sensussiana (STIKES DUTAGAMA KLATEN, 2013)
Background: Parents have a way, its own pattern of raising, guiding children. Ways and patterns of parenting between the different families with other families. The success of a person contributed approximately 20% intellectual, remaining determined a person's ability to build relationships, self motivation and the ability to manage emotions. Objective: To determine the relationship of parenting parents with emotional intelligence management. Method: analytic observational study with cross-sectional design. The research was carried out on 2 to 30 May 2013. Population in the study of 159 parents and children. Purposive sampling technique with a number of 50 respondents Results: There was a significant relationship between the Parent Parenting with Emotional Intelligence Management of Children Aged 3-5 years. Where P = 0.009 (p < 0.05) where x2 = 13.439. Parents who apply authoritative parenting good emotional intelligence, emotional intelligence is quite authoritarian, permissive while good emotional intelligence. Conclusion: There is a parenting parents relationships with intelligence emotional management of children aged 3-5 years.